CAR-T cells neurotoxicity from consolidated practice in hematological malignancies to fledgling experience in CNS tumors: fill the gap - Gatto, Lidia; Ricciotti, Ilaria; Tosoni, Alicia; Di Nunno, Vincenzo; Bartolini, Stefania; Ranieri, Lucia; Franceschi, Enrico (Frontiers in Oncology, 2023)
Chimeric antigen receptor (CAR-T) therapy has marked a paradigm shift in the treatment of hematological malignancies and represent a promising growing field also in solid tumors. Neurotoxicity is a well‐recognized common complication of CAR-T therapy and is at the forefront of concerns for CAR-based immunotherapy widespread adoption, as it necessitates a cautious approach. The non-specific targeting of the CAR-T cells against normal tissues (on-target off-tumor toxicities) can be life-threatening; likewise, immune-mediate neurological symptoms related to CAR-T cell induced inflammation in central nervous system (CNS) must be precociously identified and recognized and possibly distinguished from non-specific symptoms deriving from the tumor itself. The mechanisms leading to ICANS (Immune effector Cell-Associated Neurotoxicity Syndrome) remain largely unknown, even if blood-brain barrier (BBB) impairment, increased serum and CSF levels of cytokines, as well as endothelial activation are supposed to be involved in neurotoxicity development. Glucocorticoids, anti-IL-6, anti-IL-1 agents and supportive care are frequently used to manage patients with neurotoxicity, but clear therapeutic indications, supported by high-quality evidence do not yet exist. Since CAR-T cells are under investigation in CNS tumors, including glioblastoma (GBM), understanding of the full neurotoxicity profile in brain tumors and expanding strategies aimed at limiting adverse events become imperative. Education of physicians for assessing individualized risk and providing optimal management of neurotoxicity is crucial to make CAR-T therapies safer and adoptable in clinical practice also in brain tumors.